2013
DOI: 10.4236/ape.2013.34031
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity and Minimal Detectable Change of a New Multi-Change of Directionagility Test for Soccer Players

Abstract: This study examined the test-retest reliability, validity and external responsiveness of a new multi-change of direction agility test (NMAT) designed for soccer players. Forty-four Tunisian soccer players were recruited and were divided into two groups according to their playing levels (International, n = 21 and National, n = 23). Following familiarization, athletes performed squat jump (SJ), countermovement jump (CMJ), running speed test (5 m and 20 m), 15-m agility run (Agility-15 m), 15-m ball dribbling (Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Given the importance of the repeated change of direction ability in soccer, it is important to apply specific tests which really measured this skill in a player’s assessment. Currently, S-RSA ( Bangsbo, 1994 ) and NMAT ( Brahim, Bougatfa & Amri, 2013 ) are commonly used to assess the change of direction in soccer players. However, NMAT only assesses one sprint, whilst players need to do it multiple times during the match ( Chaouachi et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of the repeated change of direction ability in soccer, it is important to apply specific tests which really measured this skill in a player’s assessment. Currently, S-RSA ( Bangsbo, 1994 ) and NMAT ( Brahim, Bougatfa & Amri, 2013 ) are commonly used to assess the change of direction in soccer players. However, NMAT only assesses one sprint, whilst players need to do it multiple times during the match ( Chaouachi et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, S-RSA tests (also known as the Bangsbo test) have been set up with nonspecific changes of direction than those performing in the match and do not include other actions ( e.g ., run backwards or sideways) ( Bloomfield, Polman & O’Donoghue, 2007 ). In this sense, a new Multi-Change of Direction Agility test (NMAT) has been proposed as a soccer-specific field test since it allows assessing players’ change of direction as it occurs in a match ( Brahim, Bougatfa & Amri, 2013 ). Unlike the S-RSA and RSA, the NMAT allows for a specific evaluation of the soccer player since jump, acceleration, braking, and lateral and back displacement are included in the test.…”
Section: Introductionmentioning
confidence: 99%
“…Při výběru adekvátního testu může být trenérům překážkou vysoký počet existujících reaktivních a nereaktivních testových protokolů, které jsou v současné době široce využívány a ověřeny jako validní a reliabilní ("Illionois, L-Run, Pro-Agility, T-test a 505") (Stewart, Turner & Miller, 2014). Navíc stále vznikají nové testové protokoly agility, které se taktéž ukazují jako validní a reliabilní (Bidaurrazaga-Letona et al, 2015;Brahim, Bougatfa & Amri, 2013;Fessi et al, 2016;Kutlu, Yapici, Yoncalik, & Çelik, 2012). Testové protokoly by tak měly být aplikovány na základě rozboru nároků herního výkonu, které by měl daný test replikovat (Stewart et al, 2014) Brown (2012) ověřoval ve své studii "Lane agility test", který se využívá při draftu hráčů basketbalu do NBA.…”
Section: Problematika Validity Motorických Testů Hodnotících úRoveň Runclassified
“…A test battery composed of 9 tests used by German clubs was evaluated by Lottermann et al (2003) and Höner and Roth (2010), where they found that the reliability of the exercise is as follows: dribbling r = 0.49, which is a very low value and similar results were obtained by Höner et al (2009) who measured the reliability of the dribbling test in the range of 2004-2008 and its value varied and changed during these 4 years at intervals r = 0.42 -0.51. Brahim, Bougatfa & Amri (2013) evaluated the players in the Ball-NMAT (New Multi-Change Direction Agility Test) test by Mujika et al (2009) using the ICC, and which also evaluated CI (Stability Interval) and SEM (Standard Measurement Error). The results of these authors showed a high correlation r = 0.97, CI = 0.94 -0.98 and SEM had a value of 0.09.…”
Section: Agility Testmentioning
confidence: 99%